TANGGUNG JAWAB KOMISI PEMILIHAN UMUM ATAS HAK MEMILIH YANG TIDAK TERDAFTAR DALAM DAFTAR PEMILIHAN TETAP (STUDI KASUS DI DESA CIMEKAR KECAMATAN CILEUNYI KABUPATEN BANDUNG) - Dany Yulianingsih; Rasji Rasji (Jurnal Hukum Adigama, 2019)
The general election regulated in constitution No 7 on 2017  in a manner implemented one, freely,secretly, and  fair is one important element because  in the general election apart from the mechanism for  selecting leaders to  guarate periodic chanfe in leadership. This is a manifestation of the from of political night of citizens. Because Indonesia is one of the countries which uphotls human rights (HAM). In a state responsibilities for  implementation and who registered the data  vote in pemilukada, updating vote data based on population data  prepared and submitted by the govermment for unregistered vote as potensial vote in the election can make a claim by the personality in a governing election in carry out on duty calling in conducting outreach and direction to the society, menkers of the public  who are  not registered on  the permarent votes list still can using it political right in the from  of the right to votr . that’s enogh to bring the identification card (KTP), passport or other identity that prones it is a local society or a move from another area. Letter as or transder letter for resettled residents from another regions. How ever this was not finish by election officials at the district level, so that the community still did’nt exercise their voting rights in the elections of 2015.